The Short Vowels in Islamic Texts (American Journal of Islam and Society, 1996)
lqra'! Read! Proclaim!Vowels (tahrik) are the life of the Arabic language; they breathe inits spirit (ruh). Vowels are the dynamic of the word; they regulate itsmeaning and determine for the verb its active or passive voice. Vowelsare nonlocal; "a speech sound produced without occluding, diverting, orconstructing the flow of air from the lungs," as opposed to consonants,which do all of the above. Consonants are local. They are the only lettersfound in Arabic texts, whether handwritten or printed, as in the timeof the Jahinyah. Why? We deplore it in the multifold way of our multidisciplinaryapproach, for we are not living in the very intensive oral traditionof the Jahinyah. Space, time, and communication have demandsthese days.The Qur'an and the Sunnah, those unsullied fountainheads of Islam,have reached us completely vowelized. This paper is a "complimentary"plea for bringing life (ruh) to the Arabic Islamic texts by marking the shortvowels for the sake of those members of the ummah who are in the processof learning it.In his last address, the Prophet evoked "a law which you should preserveand be firmly attached to, a law clear and positive: The Book of Godand the Sunnah."At the end of his life, Muhammad (pbuh) had about 30,000 contemporarieswho had heard and memorized the Qur'an in whole orpart. Several of them could read and write and had committed theQur'an to writing in part or in toto .... All the revelations writtenby the Prophet's scribe were collected and stored in the house of'A'isha, the Prophet's wife and daughter of Abu Bakr, the firstcaliph.'Twelve years later, 'Uthman, the third caliph, felt the need to compile astandard copy of the Qur'an that would ensure the uniform pronunciationof the Qur'anic text throughout the world. During his rule, Islam had spreadfar and wide in distant lands inhabited by diverse nationalities. The ...